2017
DOI: 10.3390/v9120372
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus and Autophagy: “All Right, Everybody Be Cool, This Is a Robbery!”

Abstract: Autophagy is an essential vacuolar process of the cell, leading to lysosomal degradation and recycling of proteins and organelles, which is extremely important in maintaining homeostasis. Multiple roles have been now associated with autophagy, in particular a pro-survival role in nutrient starvation or in stressful environments, a role in life span extension, in development, or in innate and adaptive immunity. This cellular process can also take over microorganisms or viral proteins inside autophagosomes and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 110 publications
(152 reference statements)
2
41
0
Order By: Relevance
“…To successfully colonize a host, HSV-1 must overcome the immune barriers of the human body, and for this, it has evolved multiple strategies, including the ability to block autophagy (2)(3)(4)(5)(6)(7). Autophagy is a process for selective degradation of cellular components that serves as a homeostatic mechanism of the cells (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To successfully colonize a host, HSV-1 must overcome the immune barriers of the human body, and for this, it has evolved multiple strategies, including the ability to block autophagy (2)(3)(4)(5)(6)(7). Autophagy is a process for selective degradation of cellular components that serves as a homeostatic mechanism of the cells (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…For example, autophagy removes bacteria that escape the phagosomal compartment upon phagocytosis and damaged bacterium-containing phagosomes (9,10,19,20). Virions in the cytoplasm of cells or viral components are removed via a process called virophagy (4,(21)(22)(23).…”
mentioning
confidence: 99%
“…Early infection by HCMV was also shown to stimulate autophagy while simultaneously blocking autophagosome degradation (McFarlane et al, 2011 ; Chaumorcel et al, 2012 ; Mouna et al, 2016 ). This strategy, similar to some RNA viruses described in the previous section, has been postulated to help the virus utilize autophagic membranes for its replication (Lussignol and Esclatine, 2017 ), although further study will likely be required to dissect out the true role of autophagy in this scenario. Additionally, gammaherpesviruses have been shown to also induce autophagy in a stage-dependent manner.…”
Section: Autophagy and Viral Infectionmentioning
confidence: 88%
“…However, while prior evidences indicated that herpesviruses in general prefer to inhibit autophagy, more recent data has implicated additional pro-viral roles for autophagic pathways. For example, the production of several herpesviruses including HSV-1, HCMV, and Varicella-Zoster virus (VZV) has been shown to be aided by functioning autophagy (Lussignol and Esclatine, 2017 ). Early activation of autophagy by HSV-1 was proposed to help entry of the virus into host cells, as indicated by decreased viral titers in cells pre-treated with autophagy inhibitors (Siracusano et al, 2016 ).…”
Section: Autophagy and Viral Infectionmentioning
confidence: 99%
“…Autophagy also emerged as an alternative pathway to present microbial antigens to the immune system [2]. Accordingly, some pathogens have evolved successful strategies to escape immune control or promote their replication by manipulating autophagy for their own benefit [3,4].…”
Section: Introductionmentioning
confidence: 99%